Gender and precarity in platform work: Old inequalities in the new world of work - Christine Gerber (New Technology, Work and Employment, 2022)
Platform work creates a work model that is both a curse and a blessing for vulnerable labour market segments. Based on research on female precarity, the article expects that remote platform work—so-called crowdwork—could especially attract women who need to combine income and care responsibilities. This article investigates whether women experience more precarity on crowdwork platforms than men, and why their risks differ. It analyses data from a quantitative survey with crowdworkers in Germany and the United States. The results indicate higher precarity risks for women due to care work, which are also indirectly mediated via the employment status. The higher commodification of labour and weaker social infrastructure lead to generally greater precarity risks for platform workers in the United States. The high differences between women and men in Germany underline the gendered nature of labour market dualization and precarization as well as the traditional division of housework. Policy measures should address both platform work and these structural inequalities.
Keywords: 330; care work; crowdwork; division of labour; gender; inequality; platform work; precarity; segmentation